The incorporation of the 3HP regimen for tuberculosis preventive treatment in the Brazilian health system: a secondary-database nationwide analysis - Mendes, Luiz Villarinho Pereira; Trajman, Anete; Campos, Mônica Rodrigues; Correa, Marilena Cordeiro Dias Villela; Osorio-de-Castro, Claudia Garcia Serpa (Frontiers in Medicine, 2024)
The recommendation of rifampin-based shorter -and saferregimens for tuberculosis preventive treatment (TPT) is progressively replacing monotherapy with isoniazid by different countries. The Brazilian Ministry of Health (MoH) approved the incorporation of the Rifapentine + isoniazid regimen (3HP) at the end of 2020, with free distribution in the Brazilian Unified Health System (SUS) started from the last quarter of 2021. The objectives were to describe the implementation of the IL-TB System (Information System of TPT Notification) and uptake of Rifapentine + isoniazid (3HP) and Isoniazid (6H or 9H) in Brazil. A quantitative observational and descriptive was performed using the IL-TB National System as the main data source, from January 2018 to December 2022. There was a steady increase of the number of TPT prescription quarterly throughout the period, which reflects the implementation of the system itself and the progressive adherence of the health system to the noncompulsory notification of new TPT. The substitution of isoniazid (6H or 9H) by 3HP is progressing. The 3HP regimen represented less than 4% of the total administered by the end of 2021, reaching around 30% in the second half of 2022 and 40% in the last quarters of 2022. The study points not only to the need to expand TPT in the country, but also to accelerate 3HP uptake and to encourage the municipalities to notify to the IL-TB system, since there is still a high level of underreporting.